Tolerance Development in Senior Schoolchildren in Context of Russian Inclusive Education - I. S. Samokhin; N. L. Sokolova; M. G. Sergeyeva (Научный диалог, 2017)
The development of tolerance among senior schoolchildren in the context of national inclusive education is covered. Special attention is paid to the creation of tolerant relations between classmates. The relevance of the chosen topic is determined by the implementation of the Federal law “On education in Russian Federation,” providing the use of inclusive techniques and technologies in learning and education. The ways of development of tolerance cited in six dissertations on candidacy for a scientific degree of PhD in education are presented and analyzed. The works are devoted to the development of different types of tolerance: general, ethno-cultural, communicational, gender. It is emphasized that none of the thesis examined the relation to youth with disabilities that appears to the authors to be incorrect in the context of national inclusive education. It is also noted that the majority of researchers propose to develop the tolerance of students using problem discussions. The authors are convinced that the foundation of tolerance (its formation ) must not occur in senior and even primary, but in the elementary school. In 10-11th classes one should continue to develop this quality. The research novelty lies in the criticism of the modern approach, emphasizing primarily the relative dignity of the child - his/her natural inclinations and the results achieved. It is proposed to pay more attention to the absolute dignity of every child - the ability to be, to think and feel.